Mercury intrusion method for grading characterization of ceria-zirconia coated honeycomb carrier catalyst and application thereof

CN122882290APending Publication Date: 2026-10-09YUNNAN PRECIOUS METALS LAB CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611027314.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-10
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

本发明提供的表征方法能够有效区分贯穿流道、载体骨架孔和催化涂层孔,表征结果准确,测试精度高,解决了现有技术中测试数据失真、无法指导生产的问题

Benefits of technology

本发明针对蜂窝载体催化剂的三级孔结构(贯穿流道、载体骨架孔、催化涂层孔),设计了低、中、高三段式压力梯度分级压汞测试模式,通过分段加压控制,使各压力区间分别对应不同孔径范围的孔隙测试,实现了贯穿流道、载体骨架大孔及催化涂层微孔/介孔的独立表征,解决了传统压汞法中涂层与载体孔隙信号叠加、无法分级区分的技术难题,能够准确反映催化剂的实际孔隙结构特征,显著提升了表征结果的准确性与可靠性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122882290A_ABST
    Figure CN122882290A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of catalyst characterization, and provides a mercury intrusion method grading characterization method and application of a cerium-zirconium coating honeycomb carrier catalyst.The present application designs a low, medium and high three-section type pressure gradient grading mercury intrusion test mode for the three-level pore structure of the honeycomb carrier catalyst, realizes independent characterization of the through flow channel, carrier skeleton macropore and catalytic coating pore through segmented pressurization control, can accurately reflect the actual pore structure characteristics of the catalyst, and significantly improves the accuracy and reliability of the characterization results.Further, the present application calculates the pore volume of each level based on the grading test data, and establishes a quantitative correlation model of the pore structure and oxygen storage capacity.The present application solves the technical problems of signal superposition and inability to grade of the traditional mercury intrusion method, can be directly used for quality control, performance prediction and durability evaluation of catalysts in the fields of methanol reforming hydrogen production, automobile exhaust purification, industrial waste gas treatment and new energy, and has a broad application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst characterization technology, and in particular to a mercury intrusion porosimetry classification and characterization method for cerium-zirconium coated honeycomb carrier catalysts and its application. Background Technology

[0002] Cerium-zirconium coated honeycomb catalysts are widely used in methanol reforming for hydrogen production, automotive exhaust purification, industrial waste gas (VOCs) treatment, and new energy fields due to their excellent oxygen storage performance and thermal stability. The oxygen storage capacity of a catalyst (i.e., the ability of materials such as cerium oxide to release and store lattice oxygen) is one of the key indicators affecting catalytic performance. In the methanol reforming for hydrogen production, cerium-zirconium coated honeycomb catalysts mainly improve the reaction efficiency of methanol steam reforming for hydrogen production through the following mechanisms: Firstly, the oxygen storage material can provide active oxygen, effectively promoting the water-gas shift reaction (CO + H2O → CO2 + H2), converting the by-product CO into CO2 and more H2, thereby increasing hydrogen yield and product purity. Secondly, the active oxygen released by the high oxygen storage capacity can remove carbon precursors generated by methanol decomposition on the catalyst surface, inhibiting carbon deposition and effectively extending the catalyst's service life. These advantages in oxygen storage performance enable cerium-zirconium coated honeycomb catalysts to exhibit good catalytic activity and durability in applications such as methanol reforming for hydrogen production.

[0003] Cerium-zirconium coated honeycomb catalysts typically use cordierite honeycomb ceramics as the matrix, coated with a catalytic coating containing cerium-zirconium solid solution, and supported with noble metals such as platinum, palladium, and rhodium as active components. The core performance characteristics of the catalyst, such as catalytic activity, oxygen storage capacity (OSC), and anti-aging properties, are closely related to its pore structure. Specifically, the micropores and mesopores in the catalytic coating determine the number of active sites and reactant diffusion efficiency, while the macropores of the honeycomb support directly affect the overall mass transfer efficiency and mechanical stability. Therefore, accurately characterizing the pore structure of cerium-zirconium coated honeycomb catalysts and clarifying the pore characteristics and relationships between the coating and the support are of great significance for optimizing the catalyst preparation process, regulating performance, and adapting to different application scenarios.

[0004] Mercury intrusion porography (MIP) is a core method for determining the pore size distribution and pore structure of porous materials, and it is also a commonly used technique for characterizing the pore structure of catalysts. Its principle is based on the non-wetting property of mercury in most solid materials; by applying pressure, mercury is forced into the pores, with larger pressures required for smaller pore sizes. Using the Washburn equation, key parameters such as pore size distribution, pore volume, and specific surface area can be calculated, and pore connectivity can be evaluated through mercury intrusion-retraction curves.

[0005] Existing mercury intrusion porosimetry (MIP) methods typically only provide overall parameters such as total pore volume and average pore size. Because the pore size distribution of the macropores (skeletal pores) in the honeycomb carrier partially overlaps with that of the micropores and mesopores in the catalyst coating, the obtained pore signal is a superposition of the coating and carrier pores. This fails to effectively distinguish between the three distinct pore structure parameters: the through-channels, the carrier skeleton pores, and the catalyst coating pores. Consequently, the characterization results cannot accurately reflect the actual contribution of each pore level in the catalyst, thus affecting the accuracy of the test data and its engineering application value. Summary of the Invention

[0006] In view of this, the present invention provides a mercury intrusion porosimetry (MIP) method for classifying and characterizing cerium-zirconium coated honeycomb support catalysts and its application. The characterization method provided by the present invention can effectively distinguish between through-channels, support framework pores, and catalyst coating pores, providing accurate characterization results and high testing precision, thus solving the problems of distorted test data and inability to guide production in existing technologies.

[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution: A method for graded characterization of a cerium-zirconium coated honeycomb support catalyst using mercury porosimetry includes the following steps: The cerium-zirconium coated honeycomb support catalyst block is degassed and then placed in a sample tube of a mercury porosimeter for graded mercury porosimetry testing; the graded mercury porosimetry testing includes a continuous low-pressure stage, a medium-pressure stage, and a high-pressure stage; in the low-pressure stage, the test pressure is increased from an initial pressure to 0.1 MPa at a pressurization rate of 0.005~0.01 MPa / min, where the initial pressure is less than 0.1 MPa; in the medium-pressure stage, the test pressure is increased from 0.1 MPa to 10 MPa at a pressurization rate of 0.05~0.1 MPa / min; in the high-pressure stage, the test pressure is increased from 10 MPa to 200 MPa at a pressurization rate of 0.1~0.2 MPa / min. Based on the test results of the low-pressure stage, medium-pressure stage, and high-pressure stage, the pore structure parameters of the through-channel, macropores of the support skeleton, and pores of the coating in the cerium-zirconium coated honeycomb support catalyst were obtained.

[0008] Preferably, the cerium-zirconium coated honeycomb carrier catalyst block has dimensions of 10×10×20mm; the inner diameter of the mercury porosimeter sample tube matches the size of the cerium-zirconium coated honeycomb carrier catalyst block. The degassing is performed under vacuum; the degassing temperature is 80~120℃, the time is 4~6h, and the atmosphere for vacuum degassing is nitrogen or an inert gas.

[0009] Preferably, the pore size classification thresholds for the through-flow channel, the carrier skeleton macropores, and the coating pores are as follows: the pore size of the through-flow channel is >100μm, the pore size of the carrier skeleton macropores is 10~100μm, and the pore size of the coating pores is 5nm~10μm.

[0010] Preferably, the pore volume and pore size distribution of the through-channels in the cerium-zirconium coated honeycomb carrier catalyst are obtained based on the test results during the low-pressure stage, and the pore volume of the through-channels is denoted as V. 流道 Based on the test results during the medium-pressure stage, the pore volume and pore size distribution of the macropores in the cerium-zirconium coated honeycomb catalyst were obtained, and the pore volume of the macropores in the carrier framework was denoted as V. 载体 Based on the test results of the high-pressure stage, the pore volume and pore size distribution of the cerium-zirconium coated honeycomb support catalyst were obtained, and the pore volume of the coating pores was denoted as V. 涂层 .

[0011] Preferably, V is obtained. 流道 V 载体 and V 涂层 The calculation also includes determining the total pore volume of the cerium-zirconium coated honeycomb catalyst, denoted as V. 总 The method for calculating the total pore volume is shown in Equation I: V 总 =V 流道 +V 载体 +V 涂层 Formula I.

[0012] Preferably, V is obtained. 涂层 The process also includes calculating the surface oxygen storage capacity and bulk oxygen storage capacity of the cerium-zirconium coated honeycomb carrier catalyst; the method for calculating the surface oxygen storage capacity is shown in Equation II: sOSC=V 涂层 / m cat Formula II; In Formula II, sOSC represents the surface oxygen storage capacity. m cat This indicates the mass of the cerium-zirconium coated honeycomb carrier catalyst block; The method for calculating the bulk oxygen storage capacity is shown in Equation III: tOSC=V 载体 / m cat Formula III; In Formula III, tOSC represents the bulk oxygen storage capacity. m cat This indicates the mass of the cerium-zirconium coated honeycomb carrier catalyst block.

[0013] Preferably, a V coating and a V coating are obtained. 载体 The process also includes calculating the total oxygen storage capacity of the cerium-zirconium coated honeycomb carrier catalyst; the method for calculating the total oxygen storage capacity is shown in Equation IV: OSC = (V 涂层 +V 载体 ) / m cat Formula IV; In Formula IV, OSC represents the total oxygen storage capacity. m cat This indicates the mass of the cerium-zirconium coated honeycomb carrier catalyst block.

[0014] This invention also provides the application of the mercury intrusion porosimetry classification and characterization method described above in the quality control of cerium-zirconium coated honeycomb carrier catalysts.

[0015] Preferably, the quality control of the cerium-zirconium coated honeycomb carrier catalyst includes catalyst coating quality control, oxygen storage performance testing, or durability assessment.

[0016] Preferably, the threshold set in the quality control of the catalyst coating is: catalyst coating pore volume ≥ 0.25 cm³. 3 / g, pore size distribution in the range of 5~20nm; The threshold set in the oxygen storage performance test is: surface oxygen storage capacity (sOSC) ≥ 0.08 cm³. 3 / g, bulk oxygen storage capacity (tOSC) ≥ 0.12cm 3 / g, Total Oxygen Storage (OSC) ≥ 0.20cm³ 3 / g; The durability assessment specifically involves testing the pore volume retention rate of the cerium-zirconium coated honeycomb carrier catalyst after high-temperature aging. The threshold values ​​set for the durability assessment are: coating pore volume retention rate ≥ 85% and carrier skeleton pore volume retention rate ≥ 90%.

[0017] This invention provides a mercury porosimetry (MIP) method for the graded characterization of a cerium-zirconium coated honeycomb catalyst, comprising the following steps: degassing the cerium-zirconium coated honeycomb catalyst block, and then placing it in a sample tube of a mercury porosimeter for graded MIP testing; the graded MIP testing includes a continuous low-pressure stage, a medium-pressure stage, and a high-pressure stage; in the low-pressure stage, the test pressure is increased from the initial pressure to 0.1 MPa at a pressurization rate of 0.005~0.01 MPa / min, wherein the initial pressure is less than 0.1 MPa; in the medium-pressure stage, the test pressure is increased from 0.1 MPa to 10 MPa at a pressurization rate of 0.05~0.1 MPa / min; in the high-pressure stage, the test pressure is increased from 10 MPa to 200 MPa at a pressurization rate of 0.1~0.2 MPa / min; based on the test results of the low-pressure stage, the medium-pressure stage, and the high-pressure stage, the pore structure parameters of the through-channels, the macropores of the support skeleton, and the coating pores in the cerium-zirconium coated honeycomb catalyst are obtained, respectively. The beneficial effects of this invention are: This invention addresses the three-level pore structure (through-flow channels, carrier framework pores, and catalyst coating pores) of honeycomb supported catalysts. It designs a three-stage pressure gradient mercury intrusion porosimetry (MIP) mode with low, medium, and high pressure gradients. By controlling the pressure in stages, each pressure range corresponds to pore size ranges, enabling independent characterization of through-flow channels, macropores in the carrier framework, and micropores / mesopores in the catalyst coating. This solves the technical problem of superimposed and indistinguishable pore signals between the coating and carrier in traditional mercury intrusion porosimetry, accurately reflecting the actual pore structure characteristics of the catalyst and significantly improving the accuracy and reliability of the characterization results.

[0018] Traditional mercury intrusion porosimetry does not have a dedicated pore size classification threshold and pore volume allocation algorithm designed for the structural characteristics of honeycomb carriers. The test data cannot be directly used to accurately calculate key performance indicators of catalysts such as surface oxygen storage capacity, bulk oxygen storage capacity, coating bonding strength, and anti-sintering, making it difficult to guide industrial production and catalyst optimization.

[0019] Based on staged mercury intrusion porosimetry test data, this invention further designs a staged pore volume calculation method and establishes a quantitative correlation model between the pore structure parameters of cerium-zirconium coated honeycomb carrier catalyst and core performance indicators such as surface oxygen storage capacity (sOSC), bulk oxygen storage capacity (tOSC), and total oxygen storage capacity (OSC). This directly transforms the test data into quality control parameters required for industrial production, providing a direct scientific basis for optimizing the preparation process, regulating the performance, and analyzing the failure of cerium-zirconium coated catalysts, and solving the problem of the disconnect between existing test methods and engineering requirements.

[0020] The characterization method provided by this invention is applicable to various honeycomb supported catalysts (cordierite, metals, mullite, etc.) and can be widely used in the characterization, process optimization, performance screening, and lifetime prediction of cerium-zirconium coated honeycomb supported catalysts in fields such as methanol reforming for hydrogen production, automobile exhaust purification, industrial waste gas (VOCs) treatment, and new energy. It has strong practicality and promotion value; moreover, it is simple to operate, cost-controllable, and can be tested using a conventional mercury porosimeter. The testing process is standardized, which facilitates industrial-scale application and reduces the cost of catalyst characterization.

[0021] This invention also provides the application of the characterization method described above in the quality control of cerium-zirconium coated honeycomb carrier catalysts, and further sets catalyst coating quality control thresholds, oxygen storage performance thresholds and durability judgment standards based on graded characterization data, forming a complete catalyst quality evaluation system that can be directly used for catalyst performance screening, batch quality control and lifetime prediction in industrial production, and has clear engineering application value. Attached Figure Description

[0022] Figure 1 A schematic flowchart of the mercury intrusion porosimetry classification and characterization method for cerium-zirconium coated honeycomb carrier catalysts provided by the present invention. Detailed Implementation

[0023] This invention provides a mercury porosimetry (MIP) method for the graded characterization of cerium-zirconium coated honeycomb catalysts, comprising the following steps: Degassing the cerium-zirconium coated honeycomb catalyst block, then placing it in a sample tube of a mercury porosimeter for graded MIP testing; the graded MIP testing includes a continuous low-pressure stage, a medium-pressure stage, and a high-pressure stage; in the low-pressure stage, the test pressure is increased from an initial pressure to 0.1 MPa at a pressurization rate of 0.005~0.01 MPa / min, wherein the initial pressure is less than 0.1 MPa; in the medium-pressure stage, the test pressure is increased from 0.1 MPa to 10 MPa at a pressurization rate of 0.05~0.1 MPa / min; in the high-pressure stage, the test pressure is increased from 10 MPa to 200 MPa at a pressurization rate of 0.1~0.2 MPa / min. Based on the test results of the low-pressure stage, medium-pressure stage, and high-pressure stage, the pore structure parameters of the through-channel, macropores of the support skeleton, and pores of the coating in the cerium-zirconium coated honeycomb support catalyst were obtained.

[0024] Figure 1 This is a schematic flowchart of the mercury intrusion porosimetry classification and characterization method for cerium-zirconium coated honeycomb carrier catalysts provided by the present invention. The following is in conjunction with... Figure 1 Please provide a detailed explanation.

[0025] This invention degassing a cerium-zirconium coated honeycomb catalyst block. In this invention, the cerium-zirconium coated honeycomb catalyst block has dimensions of 10×10×20mm. Specifically, the cerium-zirconium coated honeycomb catalyst block is obtained by integrally cutting from a cerium-zirconium coated honeycomb catalyst, ensuring the complete preservation of the carrier's through-flow channels, carrier skeleton, and the intact structure of the catalyst coating during cutting, avoiding mechanical damage that could destroy the pore structure. This invention does not impose special requirements on the cerium-zirconium coated honeycomb catalyst; any cerium-zirconium coated honeycomb catalyst well-known to those skilled in the art can be tested using the method of this invention. The honeycomb carrier used can specifically be cordierite, metal, mullite, etc.

[0026] In this invention, the degassing is preferably vacuum degassing; the degassing temperature is preferably 80~120℃, specifically 80℃, 100℃, or 120℃; the vacuum degassing time is preferably 4~6 hours, specifically 4, 5, or 6 hours; the vacuum degassing atmosphere is preferably nitrogen or an inert gas, wherein the inert gas can be argon; the vacuum degassing is preferably carried out in a vacuum drying oven; this invention removes moisture and impurities from the sample surface and pores through vacuum degassing. Simultaneously, through vacuum pretreatment, this invention can maximize the stability of the sample state and reduce shrinkage caused by moisture / impurity removal during testing, thereby avoiding the impact of sample shrinkage on the test results.

[0027] After degassing, the degassed sample is placed in a mercury porosimeter sample tube for graded mercury porosimetry testing. In this invention, the inner diameter of the mercury porosimeter sample tube matches the size of the cerium-zirconium coated honeycomb carrier catalyst block sample. In a specific embodiment of this invention, the mercury porosimeter sample tube is a circular pipe, the size of which is designed to completely fill the cerium-zirconium coated honeycomb carrier catalyst block sample, ensuring that the mercury liquid can uniformly wet the sample surface and all pores, without any dead spots or mercury liquid overflow, ensuring that the pores are completely filled with mercury liquid during the test, and improving the accuracy of the test data.

[0028] In this invention, the mercury porosimeter used for the graded mercury porosimeter test is an AutoPore 9605 model, in intrusion mode.

[0029] In this invention, the graded mercury intrusion porosimetry test includes a continuous low-pressure stage, a medium-pressure stage, and a high-pressure stage.

[0030] In this invention, the test pressure in the low-pressure stage is increased from the initial pressure to 0.1 MPa. The initial pressure is <0.1 MPa, specifically 0.01~0.05 MPa, and the pressurization rate is 0.005~0.01 MPa / min, specifically 0.005, 0.006, 0.008 or 0.01 MPa / min. The pressure range in the low-pressure stage only allows the liquid mercury to enter the through-channels (pore size range 100~500 μm) of the honeycomb carrier, which is used to test the pore volume and pore size distribution of the through-channels. This parameter directly corresponds to the size of the gas diffusion channel and the pressure loss performance of the catalyst.

[0031] In this invention, the test pressure in the medium-pressure stage is increased from 0.1 MPa to 10 MPa, and the pressurization rate is 0.05~0.1 MPa / min, specifically 0.05, 0.06, 0.08 or 0.1 MPa / min; the pressure range of the medium-pressure stage allows the mercury liquid to enter the macropores of the carrier skeleton (pore size range 10~100 μm), which is used to test the pore volume and pore size distribution of the macropores of the carrier skeleton. These parameters correspond to the porosity of the carrier and the number of adhesion sites of the catalytic coating.

[0032] In this invention, the test pressure in the high-pressure stage is increased from 10 MPa to 200 MPa, and the pressurization rate is 0.1~0.2 MPa / min, specifically 0.1, 0.12, 0.15 or 0.2 MPa / min. The pressure range of the high-pressure stage allows the mercury liquid to enter the mesopores and micropores (pore size range 5 nm~10 μm) of the catalytic coating, which is used to test the pore volume and pore size distribution of the catalytic coating. This parameter directly corresponds to the number of active sites, oxygen storage capacity and reaction efficiency of the catalyst.

[0033] The graded mercury intrusion porosimetry test conditions set in this invention are adapted to the pore size distribution characteristics of cerium-zirconium coatings and honeycomb carriers, which can improve the accuracy and reliability of the characterization results.

[0034] In a specific embodiment of the present invention, a mercury intrusion porosimeter is used for continuous testing during the testing process. The pressure is applied sequentially, and the pressure application rate is controlled to avoid sudden pressure rises that could damage the pore structure. At the same time, the stability of the mercury intrusion process is ensured. The volume of mercury liquid intrusion under different pressures is recorded in real time to obtain independent test data for the three-level pore structure. This avoids data superposition interference between different types of pore structures and improves the repeatability of the test data.

[0035] In this invention, the pore size classification thresholds for the through-flow channels, the macropores of the support framework, and the coating pores are as follows: the pore size of the through-flow channels is >100 μm, the pore size of the macropores of the support framework is 10~100 μm, and the pore size of the coating pores is 5 nm~10 μm. This invention, combining the pore structure characteristics and performance requirements of cerium-zirconium coated honeycomb support catalysts, sets pore size classification thresholds for a three-tiered pore structure to ensure accurate differentiation between different types of pore structures.

[0036] In this invention, based on the test results of the low-pressure, medium-pressure, and high-pressure stages, the pore structure parameters of the through-channels, macropores of the support framework, and pores of the coating in the cerium-zirconium coated honeycomb support catalyst are obtained, respectively. These pore structure parameters include pore volume, pore size distribution, and specific surface area. Specifically, based on the test results of the low-pressure stage, the pore volume and pore size distribution of the through-channels in the cerium-zirconium coated honeycomb support catalyst are obtained, and the pore volume of the through-channels is denoted as V. 流道 Based on the test results during the medium-pressure stage, the pore volume and pore size distribution of the macropores in the cerium-zirconium coated honeycomb catalyst were obtained, and the pore volume of the macropores in the carrier framework was denoted as V. 载体 Based on the test results of the high-pressure stage, the pore volume and pore size distribution of the cerium-zirconium coated honeycomb support catalyst were obtained, and the pore volume of the coating pores was denoted as V. 涂层 .

[0037] In a specific embodiment of the present invention, based on the individual characterization curves of the honeycomb carrier and the cerium-zirconium coating, a first grading threshold (10 μm) and a second grading threshold (5 nm) are set to extract the structural parameters of the macropores of the carrier and the mesopores of the coating, respectively.

[0038] In a specific embodiment of the present invention, the pore connectivity of the cerium-zirconium coated honeycomb carrier catalyst can be calculated by the mercury intrusion volume change rate at different pressure ranges.

[0039] In this invention, V is obtained. 流道 V 载体 and V 涂层 The calculation also includes determining the total pore volume of the cerium-zirconium coated honeycomb catalyst, denoted as V. 总The method for calculating the total pore volume is shown in Equation I: V 总 =V 流道 +V 载体 +V 涂层 Formula I.

[0040] In this invention, V 总 V 流道 V 载体 V 涂层 The units are all cm 3 / g.

[0041] In this invention, V is obtained. 涂层 The process also includes calculating the surface oxygen storage capacity and bulk oxygen storage capacity of the cerium-zirconium coated honeycomb carrier catalyst; the method for calculating the surface oxygen storage capacity is shown in Equation II: sOSC=V 涂层 / m cat Formula II; In Formula II, sOSC represents the surface oxygen storage capacity. m cat This indicates the mass of the cerium-zirconium coated honeycomb carrier catalyst block sample; The method for calculating the bulk oxygen storage capacity is shown in Equation III: tOSC=V 载体 / m cat Formula III; In Formula III, tOSC represents the bulk oxygen storage capacity. m cat This indicates the mass of the cerium-zirconium coated honeycomb carrier catalyst block sample.

[0042] In this invention, V is obtained. 涂层 and V 载体 The process also includes calculating the total oxygen storage capacity of the cerium-zirconium coated honeycomb carrier catalyst; the method for calculating the total oxygen storage capacity is shown in Equation IV: OSC = (V 涂层 +V 载体 ) / m cat Formula IV; In Formula IV, OSC represents the total oxygen storage capacity. m cat This indicates the mass of the cerium-zirconium coated honeycomb carrier catalyst block sample.

[0043] In this invention, in formulas II, III and IV, m cat The units for all values ​​are g.

[0044] Based on the results of three-stage graded mercury intrusion porosimetry, this invention designs a proprietary graded pore volume calculation method, pore size distribution threshold, and structure-performance correlation model to realize the transformation of test data into engineering application parameters.

[0045] This invention also provides the application of the mercury intrusion porosimetry classification and characterization method described above in the quality control of cerium-zirconium coated honeycomb carrier catalysts.

[0046] In this invention, the quality control of the cerium-zirconium coated honeycomb carrier catalyst includes catalyst coating quality control, oxygen storage performance testing, or durability assessment.

[0047] In this invention, the threshold value set in the quality control of the catalyst coating is preferably: catalyst coating pore volume ≥ 0.25 cm³. 3 / g, pore size distribution in the range of 5~20nm; this threshold corresponds to catalyst coating bonding strength ≥2MPa and coating peeling rate <0.2%, which can effectively avoid the decrease in catalyst efficiency caused by coating peeling.

[0048] In this invention, the threshold set in the oxygen storage performance test is: surface oxygen storage capacity (sOSC) ≥ 0.08 cm³. 3 / g, bulk oxygen storage capacity (tOSC) ≥ 0.12cm 3 / g, Total Oxygen Storage (OSC) ≥ 0.20cm³ 3 / g; This threshold can meet the catalytic performance requirements of scenarios such as automobile exhaust purification, industrial waste gas treatment, and new energy batteries.

[0049] In this invention, the durability assessment specifically involves testing the pore volume retention rate of the cerium-zirconium coated honeycomb carrier catalyst after high-temperature aging. The threshold values ​​set for the durability assessment are: coating pore volume retention rate ≥ 85% and carrier skeleton pore volume retention rate ≥ 90%. These threshold values ​​can be used as criteria for determining whether the catalyst meets the requirements for anti-sintering and anti-poisoning performance, and can be used for catalyst failure analysis and service life prediction. In this invention, the preferred conditions for high-temperature aging are: temperature 800~1000℃ and time 100h.

[0050] In this invention, the characterization method of this invention can also be used in conjunction with the conversion rate of carbon monoxide (CO) and nitrogen oxides (NO) of the catalyst. x The evaluation is based on factors such as conversion rate.

[0051] The mercury intrusion porosimetry (MIP) method of this invention is used for quality control of cerium-zirconium coated honeycomb carrier catalysts. Specifically, it can be applied to automotive exhaust purification, industrial waste gas treatment, or catalyst anti-aging evaluation. In automotive exhaust purification, the characterization method of this invention can be used to characterize cerium-zirconium coated honeycomb carrier catalysts, providing reference data for optimizing the preparation process (optimizing coating thickness, calcination temperature, and carrier pretreatment). In industrial waste gas treatment, the optimal catalyst can be screened by comparing the correlation between hierarchical pore parameters and catalytic performance. In catalyst anti-aging evaluation, the catalyst's lifespan and replacement cycle can be predicted by tracking changes in the hierarchical pore structure before and after aging.

[0052] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0053] Example 1 1. Sample preparation Cordierite honeycomb carrier catalyst (200 mesh, 0.2 mm wall thickness) was selected. A 10×10×20 mm block sample was taken using the whole sampling method. The sample mass was 1 g, ensuring that the sample was undamaged and the coating was not peeled off. The sample was placed in a vacuum drying oven and degassed at 120°C for 4 h to remove moisture and impurities from the pores. Then it was placed in a special mercury porosimetry sample tube.

[0054] 2. Mercury porosimetry test The tests were conducted using an AutoPore 9605 mercury porosimeter, following a three-stage pressure gradient. Specific test parameters and results are as follows: In the low-pressure section, the test pressure was increased from 0.01 MPa to 0.1 MPa at a rate of 0.005 MPa / min. The test was conducted through the flow channel, and the flow channel orifice volume was obtained as 0.12 cm³. 3 / g, pore size distribution 200~400μm; In the medium-pressure section, the test pressure was increased from 0.1 MPa to 10 MPa at a rate of 0.05 MPa / min. The large pores of the test carrier skeleton were examined, and a pore volume of 0.18 cm³ was obtained. 3 / g, pore size distribution 20~80μm; In the high-pressure section, the test pressure was increased from 10 MPa to 200 MPa at a rate of 0.1 MPa / min. The pore volume of the catalyst coating was tested, and a pore volume of 0.25 cm³ was obtained. 3 / g, pore size distribution 8~25nm.

[0055] 3. Data Calculation According to the graded pore volume calculation method and structure-performance correlation model of the present invention, the following is calculated: Total pore volume: V 总 =0.12 + 0.18 + 0.25 = 0.55cm 3 / g; Surface oxygen storage capacity: sOSC = 0.25 / 1 = 0.25 cm³ 3 / g; Oxygen storage capacity in bulk: tOSC = 0.18 / 1 = 0.18 cm³ 3 / g; Total oxygen storage capacity: OSC = (0.25 + 0.18) / 1 = 0.43 cm³ 3 / g; 4. Performance Verification The performance of the cordierite honeycomb supported catalyst was tested to verify the accuracy of the method of the present invention: Catalytic coating bonding strength test: The coating bonding strength is 2.3 MPa, and the peeling rate is 0.18%, which meets the quality control threshold set in this invention (catalytic coating pore volume ≥ 0.25 cm). 3 / g, corresponding to a bonding strength ≥2MPa and a shedding rate <0.2%); Catalytic performance test: Under simulated automotive exhaust conditions, the exhaust purification efficiency is 98.5%, meeting the requirements for industrial applications; Durability test: After aging the sample at 800℃ for 100h, the coating pore volume retention rate was 88% and the carrier pore volume retention rate was 92%, which met the durability judgment standard, indicating that the catalyst's anti-sintering performance was qualified.

[0056] The results of the examples show that the mercury intrusion porosimetry classification characterization method of the present invention can accurately test the tertiary pore structure of the honeycomb supported catalyst, and the test data is highly consistent with the actual performance of the catalyst, which can effectively guide the quality control and performance optimization of the catalyst.

[0057] In summary, addressing the technical limitations of existing mercury intrusion porosimetry methods in accurately and non-destructively characterizing the hierarchical pore structure of honeycomb-supported catalysts, this invention provides a mercury intrusion porosimetry characterization method that integrates sample preparation, hierarchical testing, data modeling, and performance correlation. This method improves the accuracy of pore structure testing, establishes a quantitative relationship between pore structure and the core performance of the catalyst, enhances the engineering application value of the testing method, and solves the problems of distorted test data and inability to guide production in existing technologies. It has broad application prospects.

[0058] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for mercury intrusion porosimetry classification and characterization of a cerium-zirconium coated honeycomb carrier catalyst, characterized in that, Includes the following steps: The cerium-zirconium coated honeycomb catalyst block was degassed and then placed in a mercury porosimeter sample tube for staged mercury porosimetry. The staged mercury porosimetry included a continuous low-pressure stage, a medium-pressure stage, and a high-pressure stage. In the low-pressure stage, the test pressure was increased from the initial pressure to 0.1 MPa at a pressurization rate of 0.005~0.01 MPa / min, where the initial pressure was less than 0.1 MPa. In the medium-pressure stage, the test pressure was increased from 0.1 MPa to 10 MPa at a pressurization rate of 0.05~0.1 MPa / min. In the high-pressure stage, the test pressure was increased from 10 MPa to 200 MPa at a pressurization rate of 0.1~0.2 MPa / min. Based on the test results of the low-pressure stage, medium-pressure stage, and high-pressure stage, the pore structure parameters of the through-channel, macropores of the support skeleton, and pores of the coating in the cerium-zirconium coated honeycomb support catalyst were obtained.

2. The mercury intrusion porosimetry classification and characterization method according to claim 1, characterized in that, The cerium-zirconium coated honeycomb carrier catalyst block has dimensions of 10×10×20mm; the inner diameter of the mercury porosimeter sample tube matches the size of the cerium-zirconium coated honeycomb carrier catalyst block. The degassing is performed under vacuum; the degassing temperature is 80~120℃, the time is 4~6h, and the atmosphere for vacuum degassing is nitrogen or an inert gas.

3. The mercury intrusion porosimetry classification and characterization method according to claim 1, characterized in that, The pore size classification thresholds for the through-flow channel, the carrier skeleton macropores, and the coating pores are as follows: the pore size of the through-flow channel is >100μm, the pore size of the carrier skeleton macropores is 10~100μm, and the pore size of the coating pores is 5nm~10μm.

4. The mercury porosimetry classification and characterization method according to claim 1, characterized in that, Based on the test results during the low-pressure stage, the pore volume and pore size distribution of the through-channels in the cerium-zirconium coated honeycomb carrier catalyst were obtained, and the pore volume of the through-channels was denoted as V. 流道 Based on the test results during the medium-pressure stage, the pore volume and pore size distribution of the macropores in the cerium-zirconium coated honeycomb catalyst were obtained, and the pore volume of the macropores in the carrier framework was denoted as V. 载体 Based on the test results of the high-pressure stage, the pore volume and pore size distribution of the cerium-zirconium coated honeycomb support catalyst were obtained, and the pore volume of the coating pores was denoted as V. 涂层 .

5. The mercury intrusion porosimetry classification and characterization method according to claim 4, characterized in that, Get V 流道 V 载体 and V 涂层 The calculation also includes determining the total pore volume of the cerium-zirconium coated honeycomb catalyst, denoted as V. 总 The method for calculating the total pore volume is shown in Equation I: V 总 =V 流道 +V 载体 +V 涂层 。 6. The mercury intrusion porosimetry classification and characterization method according to claim 4, characterized in that, Get V 涂层 The process also includes calculating the surface oxygen storage capacity and bulk oxygen storage capacity of the cerium-zirconium coated honeycomb carrier catalyst; the method for calculating the surface oxygen storage capacity is shown in Equation II: sOSC=V 涂层 / m cat Formula II; In Formula II, sOSC represents the surface oxygen storage capacity. m cat This indicates the mass of the cerium-zirconium coated honeycomb carrier catalyst block; The method for calculating the bulk oxygen storage capacity is shown in Equation III: tOSC=V 载体 / m cat Formula III; In Formula III, tOSC represents the bulk oxygen storage capacity. m cat This indicates the mass of the cerium-zirconium coated honeycomb carrier catalyst block.

7. The mercury intrusion porosimetry classification and characterization method according to claim 4, characterized in that, Obtain V coating and V 载体 The process also includes calculating the total oxygen storage capacity of the cerium-zirconium coated honeycomb carrier catalyst; the method for calculating the total oxygen storage capacity is shown in Equation IV: OSC = (V 涂层 + V 载体 ) / m cat Formula IV; In Formula IV, OSC represents the total oxygen storage capacity. m cat This indicates the mass of the cerium-zirconium coated honeycomb carrier catalyst block.

8. The application of the mercury intrusion porosimetry classification and characterization method according to any one of claims 1 to 7 in the quality control of cerium-zirconium coated honeycomb carrier catalysts.

9. The application according to claim 8, characterized in that, The quality control of the cerium-zirconium coated honeycomb carrier catalyst includes catalyst coating quality control, oxygen storage performance testing, or durability assessment.

10. The application according to claim 9, characterized in that, The threshold set for the quality control of the catalyst coating is: catalyst coating pore volume ≥ 0.25 cm³. 3 / g, pore size distribution in the range of 5~20nm; The threshold set in the oxygen storage performance test is: surface oxygen storage capacity (sOSC) ≥ 0.08 cm³. 3 / g, bulk oxygen storage capacity (tOSC) ≥ 0.12cm 3 / g, Total Oxygen Storage (OSC) ≥ 0.20cm³ 3 / g; The durability assessment specifically involves testing the pore volume retention rate of the cerium-zirconium coated honeycomb carrier catalyst after high-temperature aging. The threshold values ​​set for the durability assessment are: coating pore volume retention rate ≥ 85% and carrier skeleton pore volume retention rate ≥ 90%.